(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2022)
African universities have been largely dominated and shaped by the colonial trajectory and organized in accordance with the Occidental model. With remaining epistemologically subservient to the Western hegemony, they played a great deal in the practice of epistimicide in the continent. Their history of establishment, as an institute that produces the necessary manpower for the smooth functioning of the colonial enterprise, have still kept defining their essence in another form, i.e., alienation. Characterized by a dismantlement of everything that is local, the universities in the continent pronounced the modernization discourse that made Africa lose specificity rather an entity that need to be studied by analogy. Moreover, for its intrinsically alienated underpinning, the type of university that many African countries inherited and developed anew have only used them for being a periphery at the global stage of knowledge generation. Overcoming such a challenge, this piece, with the help of analyzing intensive literature and deployment of a discursive reasoning approach, embarks on the idea of decolonization. Fundamental to the notion of decolonization here is the epistemological decolonization of the continent via its institutions of higher learning and finding a discursive space where the universities assure subjectivity that allows them to harness the local context and respond to the demands thereof. To this effect, Philosophy, and perhaps African philosophy specifically, despite an endless debate of proving its existence, have assumed an indispensable role in empowering Africans through articulating philosophical locus taking in to account the context and cultural idiosyncrasies of the African. It is further tasked in broadening the horizons of subjectivity, decolonization, and independence of the continent at large which still remained only at the flag level.